Usability Testing on Android-based KMS for Pregnant Women using the USE Questionnaire - Halimah Tus Sadiah (Research Collaboration Community (RCC), 2020)
An Android-based medicines knowledge management system (KMS) application has been built as a result of a research about the usage of medicines on pregnant women. Usability testing is needed to be used to measure the success rate of the implementation of this mobile application. In this study, the Usefulness, Satisfaction and Ease of Use (USE) Questionnaire method is used, with quantitative and qualitative analysis. Based on the test results, it shows that the KMS application for pregnant women has a high usability result, with each component score, namely Usefulness reaches 86%, Ease of Use of 86%, and Satisfaction of 84%. On average, 85% indicates that the Android-based medicines KMS application for pregnant women has high quality attributes in ease of use. In addition, this application already has criteria to meet the needs of users, especially pregnant women, to easily find information and knowledge about medicines that are safe to consume during pregnancy to relieve pain or pregnancy complaints.